PENGARUH MINAT DAN MOTIVASI MEMBACA TERHADAP KEMAMPUAN MENULIS CERPEN SISWA KELAS XII SMK NEGERI 9 SAMARINDA - Pontjo Wulan H.I. (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2019)
This study aims to determine the influence of (1) reading interest, (2) reading motivation, and (3) reading motivation and interest on short story writing skills. This is a quantitative research and uses correlational analysis. The data collection is analyzed using inferential and descriptive statistics. The result shows there is positive and significant influence of reading interest, reading motivation, reading interest and motivation on short story writing skills.